Structure of meso- and microcycles of the preparatory period in the shooter technical training program - Pogodin V.A.; Zautorova E.V. (Пенитенциарная наука, 2023)
Introduction: the article is devoted to the issues of sports training of shooters specializing in bullet shooting. The paper presents the means and methods of sports training and determines the load and amount of training effects on the athlete. Purpose: to confirm effectiveness of the bullet shooting training program for shooters by improving periodization of the training process. Methods: theoretical analysis of literary sources; methods of synthesis and generalization; the method of mathematical statistics is the nonparametric Man-Whitney criterion. Results: the annual cycle of shooting sports training traditionally contains three macrocycles, namely the preparatory, competitive and recovery periods. The main volume of training effects occurs during the preparatory period. Distribution of mesocycles and microcycles during the preparatory period helps regulate the volume and intensity of the means and methods of technical training. The ratio of the parameters of the training work of shooters determines the structure of the technical training program. At the end of the pedagogical experiment, the subjects of the experimental group demonstrated a mathematically reliable increase in the results of shooting at the control training compared with the control group. Conclusion: when planning sports training, it is necessary to determine the place of mesocycles in the preparatory period and the place of microcycles inside mesocycles, thus ensuring the effective choice of means and methods of influencing the athlete, amount of the load and its intensity